Relation between dietary fat and energy and micronutrient intakes. Issue 5 (1st May 1997) - Tonstad, S; Sivertsen, M
Abstract : Concern has been raised about the energy and nutrient adequacy of low fat diets for children that aim to prevent cardiovascular disease in Western populations. The diets of 174 randomly chosen schoolchildren aged 8–12 years from middle and high socioeconomic groups were analysed to determine their nutrient composition in relation to fat intake. The mean percentages of energy intake from fat and saturated fat were 31 and 13%, respectively, and 44% of all children reported consuming <30% of their energy from fat. The energy intake did not change across the spectrum of fat intake. A decreased fat intake was associated with an increased sugar intake, but also with increased nutrient densities of thiamin, niacin, folate, vitamin C, magnesium, and iron, reflecting an increased intake of fruit, vegetables, and grains. Parental educational level was the most important determinant of fat intake (inverse relation). It is concluded that a self selected low fat intake among children from average to high socioeconomic backgrounds does not compromise their intake of major nutrients or energy.